The effects of ERN1 on gene expression during early rhizobial infection in Lotus japonicus - Liu, Meng; Kameoka, Hiromu; Oda, Akiko; Maeda, Taro; Goto, Takashi; Yano, Koji; Soyano, Takashi; Kawaguchi, Masayoshi (Frontiers in Plant Science, 2023)
Legumes develop root nodules in association with compatible rhizobia to overcome nitrogen deficiency. Rhizobia enter the host legume, mainly through infection threads, and induce nodule primordium formation in the root cortex. Multiple transcription factors have been identified to be involved in the regulation of the establishment of root nodule symbiosis, including ERF Required for Nodulation1 (ERN1). ERN1 is involved in a transcription network with CYCLOPS and NODULE INCEPTION (NIN). Mutation of ERN1 often results in misshapen root hair tips, deficient infection thread formation, and immature root nodules. ERN1 directly activates the expression of ENOD11 in Medicago truncatula to assist cell wall remodeling and Epr3 in Lotus japonicus to distinguish rhizobial exopolysaccharide signals. However, aside from these two genes, it remains unclear which genes are regulated by LjERN1 or what role LjERN1 plays during root nodule symbiosis. Thus, we conducted RNA sequencing to compare the gene expression profiles of wild-type L. japonicus and Ljern1-6 mutants. In total, 234 differentially expressed genes were identified as candidate LjERN1 target genes. These genes were found to be associated with cell wall remodeling, signal transduction, phytohormone metabolism, and transcription regulation, suggesting that LjERN1 is involved in multiple processes during the early stages of the establishment of root nodule symbiosis. Many of these candidate genes including RINRK1 showed decreased expression levels in Ljnin-2 mutants based on a search of a public database, suggesting that LjERN1 and LjNIN coordinately regulate gene expression. Our data extend the current understanding of the pleiotropic role of LjERN1 in root nodule symbiosis.